The effects of a serum substitute on the developmental progress and cell proliferation in bovine embryos cultured in vitro - Kotze, Dirk Jacobus (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1998.